Beyond the dermis—high-risk invasive squamous cell carcinoma: a retrospective review. (2nd October 2020) - Sood, Anshum; Bivona, Louis; Mahkzoumi, Zaineb; Hausner, Petr; Miller, Kenneth; Regine, William F; Snider, James; Ng, Vincent Y
Abstract : Objective: Most cutaneous squamous cell carcinomas (cSCC) are low risk and can be treated with simple excision or ablation. High-risk cSCC require invasive treatment, including radical surgery. We present our experience in treating invasive cSCC of the pelvis and extremities. Method: A retrospective review of the data of patients with invasive cSCC, indicated for surgery between 2014 and 2018, from a single institution was carried out. Results: A total of 19 patients (nine men, 10 women) were included in the study. Mean age was 62 years; mean tumour size was 8.6cm). Of the 19 patients, five patients with paraplegia with cSCC arising from hard-to-heal ulcers died of infection or bleeding after surgery or systemic therapy. Also, nine patients with localised cSCC underwent margin-negative resection with or without radiation; one patient experienced disease relapse. Of the participants, two patients with previous transplants and multifocal aggressive cSCC underwent numerous resections but succumbed to disease, and two patients who presented with locally recurrent disease after previous positive margin resection and radiation underwent re-resection but developed recurrent disease. Conclusions: Prognosis for invasive cSCC largely depends on clinical setting. Tumours arising from ulcers in patients with paraplegia have a poor prognosis regardless of treatment. Invasive cSCC in transplant patients are often multifocal and often recur. Debulking procedures are associated with local recurrence despite radiation. Patients presenting with localised disease have a favourable prognosis with wide resection, flap coverage and adjuvant therapy.